The Influence of Atmosphere (Store Atmosfhire) and Store Image (Store Image) on Purchasing Decisions At Toga Peak Cafe Sumedang - Nining Kurniasih; Aa Kartiwa (Journal of Bussines Management Basic, 2023)
This research was conducted at Toga Peak Cafe Sumedang, which is located in Sukajaya - South Sumedang, approximately 5 km from Sumedang city. The method used in this study is a survey method with a verification descriptive analysis approach. The Effect of Atmosphere (Store Atmosphere) on Purchasing Decisions at Toga Pak Cafe Sumedang, shows that there is a positive relationship between store atmosphere and purchasing decisions. Store atmosphere has a significant positive effect on purchasing decisions at Toga Peak Cafe Sumedang, meaning that if the store atmosphere is not considered or left unchecked, it will reduce purchasing decisions. The Effect of Store Image on Purchasing Decisions at Toga Peak Cafe Sumedang shows that there is a positive relationship between store image and purchase decisions. This means that increasing store image will increase purchasing decisions. So by increasing the superiority of characteristics or characteristics or a better store image it will influence purchasing decisions. The influence of atmosphere (Store Atmosphere X1) and Image (Store Image X2) influence Purchase decisions (Y), the path coefficient value of 0.8427 is obtained. Based on the test, it is obtained that the value of Fcount is greater than the value of Ftable, from this value it is obtained that the decision H0 is rejected, so that the Store Atmosphere variable has a significant and positive effect on the purchasing decision variable.